Conjecture mapping to support vocationally educated adult learners in open-ended tasks. Issue 3 (26th May 2020) - Boelens, Ruth; De Wever, Bram; McKenney, Susan
ABSTRACT: Background: This case reports on a teacher education course that aimed to support adult learners with a vocational education background to accomplish open-ended tasks. Conjecture mapping was used to identify the most salient design features, and to test if, how, and why these course features supported learners. Methods : Inspired by ethnographic approaches, sustained engagement and multiple data sources were used to explain the effects of the course design on participants' behavior and perceptions: student and teacher interviews, observations, and artifacts. Findings : The results reveal that almost all of the proposed design features stimulated the participants toward the intended enactment processes, which in turn yielded the intended learning outcomes. For instance, worked examples (i.e., design feature) not only engendered the production of artifacts that meet high standards (i.e., enactment process) because they clarify the task requirements, but also fostered a safe structure (i.e., enactment process) by providing an overall picture of the task. Contribution : The conjecture map resulting from this study provides a theoretical frame to describe, explain, and predict how specific course design features support vocationally educated adult learners (VEAL) in open-ended tasks, and assists those who aim to implement open-ended tasks in similar contexts.